Scottish crime and justice survey, 2021-2022 (Scottish Crime and Justice Survey, 2024)
The Scottish Crime and Justice Survey (SCJS) is a social survey which asks people about their experiences and perceptions of crime in Scotland. The survey is an important resource for both the government and public of Scotland. Respondents are selected at random from the Postal Address File and participation in the survey is entirely voluntary.